Pemberiaan Mitigasi dan Pemberdayaan Odha di Aceh Melalui Kelompok Dukungan Sebaya (KDS) Seudara - Harjoni; Nur Asyiah (CV Putra Publisher, 2023)
This service aims to provide psychological support to Key population friends and People with HIV/AIDS (ODHA) through Peer Support Groups/Social Welfare Institutions in North Aceh. Method: carried out by direct observation and interviews with North Aceh KDS/LKS with the stages namely preparation, assessment, alternative program planning, action plan formalization, implementation, and evaluation. Results: Every North Aceh KDS/LKS administrator can act as a facilitator in motivating fellow ODHA that they need psychological support for their current health condition (with HIV status). The Implementation Phase of Activities The participation of ODHA friends who are involved in the North Aceh KDS/LKS board is expected to be able to carry out program activities that can provide support to fellow ODHA friends. The collaboration between North Aceh KDS/LKS administrators, ODHA friends, and health service facilities has been going well. namely: Assistance and Outreach to Key Populations and ODHA, Facilitating Access to Health Services, Health Talks (BBS), Social Services, ODHA Home Visits, and World AIDS Day (HAS).